Evaluasi Penggunaan Obat Antihipertensi pada Pasien Rawat Jalan GGK dengan Hemodialisa di RSUP dr. Soeradji Tirtonegoro Klaten Tahun 2017 - Farah Afifah; Surya Amal (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Hypertension is one of the major risk factors for chronic renal failure because it can cause damage to blood vessels in the kidney, thus reducing the ability of the kidneys to filter blood properly. Giving and analyzing antihypertensive drugs are very important in these circumstances, as it can accelerate the progression of the disease and increase the patient's mortality rate. Rasulullah sallallaahu 'alaihi wasallam, said: „There is a cure for every disease‟. If the medicine is right for an illness, it will be healed with the permission of Allah 'Azza wajalla "(H.R. Muslim). Therefore, the aspects of efficacy and safety of drug use in patients need to be evaluated. The purpose of this study was to determine patient accuracy, drug accuracy and dose accuracy evaluated based on reference books in the use of antihypertensive therapy in outpatients with chronic renal failure with hemodialysis. This research is a descriptive research conducted at RSUP dr. Soeradji Tirtonegoro Klaten. Data were retrospective from medical records, using non-experimental methods. The patient sample was taken according to the inclusion criteria of the research by purposive sampling method. The results of this study indicate that there were 55 patients evaluated consisted of 35 men (64%) and 20 women (36%). Based on the data obtained it can be concluded that the use of antihypertensive drugs in chronic renal failure outpatients with hemodialysis at RSUP dr. Soeradji Tirtonegoro Klaten 2017 shows right patient (100%), exact medicine (90,92%) and exact dose (98,19%).